PENGARUH ANALISIS DAN PENGAWASAN KREDIT TRHADAP KREDIT MACET PADA LPD KECAMATAN MARGA - Ni Kadek Diah Sugiri Putri (UNHI Press, 2022)
This research aims to examine and analyze the effect of credit analysis and credit supervision on bad loans. The population in this research were all employees of the Village Credit Institution (LPD) in Marga District, amounting to 156 people. the technique of collection data's in this research using a questionnaire. the method of determining samples in this study using purposive sampling method,. Samples were taken as many as 88 people. The technique in the data analysis used in this research is multiple linear regression analysis. The results of this research indicate that the variables of credit analysis and credit supervision have a negative and significant effect on bad loans at the Village Credit Institution (LPD) in Marga District